PENGARUH LATIHAN ZIG-ZAG RUN TERHADAP KEMAMPUAN KELINCAHAN DRIBBLING BOLA PEMAIN FUTSAL SMA NEGERI 8 LUWU UTARA - Alrazid, Harun; Pribadi , Imam; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In a futsal game, agility is very important, especially in terms of controlling the ball under pressure from the opponent. The purpose of this study was to determine the effect of zig-zag running training on dribbling agility in SMA Negeri 8 North Luwu futsal players. A one-group pretest-posttest design was used as the research design in this experimental study. Using non-probability sampling techniques, the population and sample of this study consisted of 24 people. Three times per week was the training frequency for the zig-zag running program for six weeks. After receiving training, data analysis showed a considerable increase in dribbling agility, with a percentage increase of 21.53% which is classified as very good. Therefore, it can be said that zig-zag running training helps SMA Negeri 8 North Luwu futsal players become more proficient in dribbling.